Corneal ulceration in south-east Asia III: prevention of fungal keratitis at the village level in south India using topical antibiotics. Issue 12 (17th August 2006) - Srinivasan, M; Upadhyay, M P; Priyadarsini, B; Mahalakshmi, R; Whitcher, J P
Abstract : Aim: To determine whether topical antifungal prophylaxis distributed by paid village health workers (VHWs) in south India is necessary after corneal abrasion to prevent fungal keratitis in a population where half of the ulcers are fungal. Methods: Two panchayaths (village administrative units in Madurai district with a combined population of 48 039 were followed prospectively for 18 months by 15 VHWs who were trained to identify post-traumatic corneal abrasions. Patients fulfilling the eligibility criteria were randomised into two groups and treated with either 1% chloramphenicol and 1% clotrimazole ointment or 1% chloramphenicol and a placebo ointment three times a day for 3 days. Patients, doctors and VHWs were blinded to treatment. Results: During the 18-month period, 1365 people reported to VHWs with ocular injuries, of whom 374 with corneal abrasions were eligible for treatment. Of these, 368 (98.5%) abrasions healed without complications. Two patients had mild localised allergic reactions to the ointment, two dropped out and two patients in the placebo group developed microscopic culture-negative corneal stromal infiltrates that healed in 1 week with natamycin drops. Conclusions: Both fungal and bacterial ulcers that occur after traumatic corneal abrasions seem to be effectively prevented in a village setting using only antibiotic prophylaxis.